(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2026)
This article addresses the conception of the video mapping and performance work entitled A Report to an Academy, developed from Franz Kafka’s homonymous short story and presented in a context analogous to that of its literary reference. In three moments, the text examines the influence of the story on the author’s creative process, the resulting visual solutions, and a philosophical discussion of Kafka’s writing, analyzed as a minor operation of finding a way out through language, capable of straining instituted codes and opening other paths of sensible experience.